The alchemist - Coelho, Paulo; Clarke, Alan (Alan R.) (New York, NY : Harper Collins, 1993)
"A special 25th anniversary edition of Paulo Coehlo's extraordinary international bestselling phenomenon--the inspiring spiritual tale of self-discovery that has touched millions of lives around the world.Combing magic, mysticism, wisdom and wonder, The Alchemist has become a modern classic, selling millions of copies around the world and transforming the lives of countless readers across generations. Paulo Coelho's masterpiece tells the mystical story of Santiago, an Andalusian shepherd boy who yearns to travel in search of a worldly treasure. His quest will lead him to riches far different--and far more satisfying--than he ever imagined. Santiago's journey teaches us about the essential wisdom of listening to our hearts, of recognizing opportunity and learning to read the omens strewn along life's path, and, most importantly, to follow our dreams. "--
"This book is an English version of O Alquimista, the Portuguese original edition, published in Brazil by Editora Rocco Ltd. (Rio de Janeiro). Copyright 1988 by Paulo Coelho. Previous paperback editions were published in 1994 and 1998 by HarperOne, a division of HarperCollins Publishers. A HarperFlamingo edition was published in 1998. A previous HarperPerennial paperback edition was published in 1998 . . . . English version copyright 1993 by Paulo Coelho and Alan R. Clarke. Updated introduction copyright 2014 by HarperCollins Publishers"--Title page verso.
Keywords: FICTION / Literary; BODY, MIND & SPIRIT / Spirituality / General; BODY, MIND & SPIRIT / Inspiration & Personal Growth; Fables